2006
DOI: 10.1002/ajmg.a.31194
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical characteristics in patients with a high mutant load of the mitochondrial T8993G/C mutations

Abstract: We retrospectively analyzed the clinical, histological, and biochemical data of 11 children, five of which carried the maternally-inherited mitochondrial T8993C and six carrying the T8993G point mutations in the ATP synthase 6 gene. The percentage of heteroplasmy was 95% or higher in muscle and in blood. All patients had an early clinical presentation with muscle hypotonia, severe extrapyramidal dysfunction and Leigh disease demonstrated by the cranial MRI. A slower clinical progression and more frequent senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 26 publications
(49 reference statements)
5
63
0
2
Order By: Relevance
“…In the present study, the ATP generating enzyme complex V of the oxidative phosphorylation system was investigated. We used an enzymatic method to measure hydrolase activity of complex V, which is used in diagnosing complex V deficient patients (7). Here, we found normal expression, intact assembly, and activity of complex V in cystinotic fibroblasts with elevated cystine levels compared with fibroblasts derived from healthy controls.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the present study, the ATP generating enzyme complex V of the oxidative phosphorylation system was investigated. We used an enzymatic method to measure hydrolase activity of complex V, which is used in diagnosing complex V deficient patients (7). Here, we found normal expression, intact assembly, and activity of complex V in cystinotic fibroblasts with elevated cystine levels compared with fibroblasts derived from healthy controls.…”
Section: Discussionmentioning
confidence: 78%
“…Mitochondrial fractions of control and cystinotic fibroblasts were prepared as described before (6). Complex V activity was determined in presence and absence of specific inhibitor oligomycin (8 mg/mL) in mitochondrial fractions incubated with ATP (5 mM) as substrate (7). Briefly, the ADP generated by complex V reacts with phosphoenolpyruvic acid (1 mM) to pyruvate in the presence of pyruvate kinase (1.5 U /mL).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the clinical phenotype found in patients with nucleotide 8993 mtDNA mutations was not always typical NARP or LS and included presentations mimicking cerebral palsy or nonspecific developmental delay [Fryer et al, 1994]. The 8993C mutation was associated with a less severe phenotype, often resulting in later onset disease and slower progression [Santorelli et al, 1996;Morava et al, 2006]. Moreover, the threshold of mutant load triggering neurological disease was higher for 8993C mutation [White et al, 1999a].…”
Section: Discussionmentioning
confidence: 97%
“…To asses phenotypic variability, we examined available clinical data on all reported cases with T8993C mutation and LS using medline database searches [van Erven et al, 1987;de Vries et al, 1993;Santorelli et al, 1994Santorelli et al, , 1996Chakrapani et al, 1998;Fujii et al, 1998Fujii et al, , 2002Suzuki et al, 1998;Vilarinho et al, 2001;Hurvitz et al, 2002;Sciacco et al, 2003;Morava et al, 2006]. Developmental milestones, age at first signs, neurological and ophthalmological status at the last examination, clinical outcome, MRI, and molecular data were reviewed.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Mutation studies have shown T8993C mutation was found to be associated with a slower clinical progression and more frequent sensory neuronal involvement. 7 Also Preliminary studies have proven the utility of mutation analysis in prenatal diagnosis and of Leigh Syndrome. 8,9 Affected children presents in early life with psychomotor regression, abnormal muscle tone, weakness, brainstem and cerebellar ataxia, nystagmus, external ophthalmoplegia, ptosis, optic atrophy and decreased visual acuity, even visual loss, tachypnea, and seizures [10].…”
Section: Discussionmentioning
confidence: 99%